2012
DOI: 10.3390/ma5122521
|View full text |Cite
|
Sign up to set email alerts
|

MoO3 Thickness, Thermal Annealing and Solvent Annealing Effects on Inverted and Direct Polymer Photovoltaic Solar Cells

Abstract: Several parameters of the fabrication process of inverted polymer bulk heterojunction solar cells based on titanium oxide as an electron selective layer and molybdenum oxide as a hole selective layer were tested in order to achieve efficient organic photovoltaic solar cells. Thermal annealing treatment is a common process to achieve optimum morphology, but it proved to be damageable for the performance of this kind of inverted solar cells. We demonstrate using Auger analysis combined with argon etching that di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 50 publications
2
46
0
Order By: Relevance
“…Apart from the relatively high R series of ITO based OSC, MoO 3 might be responsible for such a low J sc . It has been reported that MoO 3 is an ideal hole transfer layer to replace PEDOT:PSS [24][25][26]28]. However, when MoO 3 is used in our ITO based OSC, its J sc is much lower than that of ITO based OSC using PEDOT:PSS as reported by our group [30].…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Apart from the relatively high R series of ITO based OSC, MoO 3 might be responsible for such a low J sc . It has been reported that MoO 3 is an ideal hole transfer layer to replace PEDOT:PSS [24][25][26]28]. However, when MoO 3 is used in our ITO based OSC, its J sc is much lower than that of ITO based OSC using PEDOT:PSS as reported by our group [30].…”
Section: Resultsmentioning
confidence: 63%
“…It was noticed that the conventional hole transfer layer (HTL), poly(3,4-ethylenedioxythiophene):poly (styrenesulfonate) (PEDOT:PSS), attacked oxide anode due to its acidic nature [24,25]. To avoid this, a thermal evaporated MoO 3 layer was used as the alternative to PEDOT:PSS in our fabrication [25][26][27][28]. After the devices fabrication, the J-V curves of ITO based and TiO 2 /Ag/TiO 2 based OSCs were measured and shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Transition‐metal oxides (TMOs) such as MoO 3 , V 2 O 5 , NiO, and WO 3 have been demonstrated successfully as replacements for the widely used HTL material such as poly(3,4‐ethylenedioxythiophene):polystyrenesulfonate (PEDOT:PSS), which is hygroscopic and acidic with an associated reduction in device stability. Among TMOs, molybdenum oxide (MoO 3 ) has emerged as a promising candidate due to high transmittance, better air stability, and high work function (WF) . Dong et al suggested that by adopting a combination of solution processing and laser direct writing roll‐to‐roll fabrication along with the simultaneous patterning of the HTL material could be enabled (Figure f).…”
Section: Laser Irradiation Of Metal Oxides and Their Applicationsmentioning
confidence: 99%
“…The ideal condition is that Rsh be as high as possible, so that the current can be transferred to the contacts of the device and not dissipated in internal losses. In these aspects, the Voc values is its relation to the organization of the active layer, but as diffusion processes of MoO3 or PEDOT:PSS and/or Ag in the active layer can also be involved in this step, this could involve recombination processes reducing the stability of these devices [46], these processes occur mainly due to the presence of Mo 5+ species, as seen by XPS analysis.…”
Section: Inverted Organic Solar Cellmentioning
confidence: 99%